Variants in the interleukin 8 gene and the response to inhaled bronchodilators in cystic fibrosis - Larissa Lazzarini Furlan; José Dirceu Ribeiro; Carmen Sílvia Bertuzzo; João Batista Salomão Junior; Dorotéia Rossi Silva Souza; Fernando Augusto Lima Marson (Elsevier, 2017)
Objective: Interleukin 8 protein promotes inflammatory responses, even in airways. The presence of interleukin 8 gene variants causes altered inflammatory responses and possibly varied responses to inhaled bronchodilators. Thus, this study analyzed the interleukin 8 variants (rs4073, rs2227306, and rs2227307) and their association with the response to inhaled bronchodilators in cystic fibrosis patients. Methods: Analysis of interleukin 8 gene variants was performed by restriction fragment length polymorphism of polymerase chain reaction. The association between spirometry markers and the response to inhaled bronchodilators was evaluated by Mann-Whitney and Kruskal-Wallis tests. The analysis included all cystic fibrosis patients, and subsequently patients with two mutations in the cystic fibrosis transmembrane conductance regulator gene belonging to classes I to III. Results: This study included 186 cystic fibrosis patients. There was no association of the rs2227307 variant with the response to inhaled bronchodilators. The rs2227306 variant was associated with FEF50% in the dominant group and in the group with two identified mutations in the cystic fibrosis transmembrane conductance regulator gene. The rs4073 variant was associated with spirometry markers in four genetic models: co-dominant (FEF25-75% and FEF75%), dominant (FEV1, FEF50%, FEF75%, and FEF25-75%), recessive (FEF75% and FEF25-75%), and over-dominant (FEV1/FVC). Conclusions: This study highlighted the importance of the rs4073 variant of the interleukin 8 gene, regarding response to inhaled bronchodilators, and of the assessment of mutations in the cystic fibrosis transmembrane conductance regulator gene. Resumo: Objetivo: A proteína interleucina 8 promove respostas inflamatórias, o que inclui sua atuação nas vias aéreas. A presença de variantes no gene da interleucina 8 causa respostas inflamatórias alteradas e possivelmente respostas variadas ao uso de broncodilatadores inalatórios. Assim, este estudo analisou as variantes da interleucina 8 (rs4073, rs2227306, rs2227307) e sua associação à resposta a broncodilatadores inalatórios em pacientes com fibrose cística. Métodos: Foi feita análise das variantes genéticas da interleucina 8 por restriction fragment length polymorphism da reação em cadeia da polimerase. A associação entre os marcadores da espirometria e a resposta a broncodilatadores inalatórios foi feita pelos testes de Mann-Whitney e Kruskal-Wallis. A análise incluiu todos os pacientes com fibrose cística e posteriormente pacientes com duas mutações no gene cystic fibrosis transmembrane conductance regulator pertencentes às Classes I a II. Resultados: Este estudo incluiu 186 pacientes com fibrose cística. Não houve associação da variante rs2227307 à resposta a broncodilatadores inalatórios. A variante rs2227306 foi associada a FEF50% no grupo dominante e no grupo com duas mutações identificadas no gene cystic fibrosis transmembrane conductance regulator. A variante rs4073 foi associada a marcadores da espirometria em quatro modelos genéticos: codominante (FEF25-75% e FEF75%), dominante (VEF1, FEF50%, FEF75% e FEF25-75%), recessivo (FEF75% e FEF25-75%) e overdominante (VEF1/CVF). Conclusões: Este estudo destaca, principalmente, a importância da variante rs4073 do gene da interleucina 8, na resposta a broncodilatadores inalatórios, concomitantemente ao genótipo das mutações no gene cystic fibrosis transmembrane conductance regulator. Keywords: CFTR, Disease severity, Interleukin 8, Lung function, Palavras-chave: CFTR, Gravidade da doença, Interleucina 8, Função pulmonar